Sobre la reconstrucción de la educación superior en Europa: Una mirada selectiva a un década, 1985-1995 - Neave, Guy (Revista Española de Pedagogía, 2018)
The evolution of higher education in Europe within the setting of the decade 1985 to 1995 is examined. The article focuses on three dimensions which have served to mould the pattern of higher education during these ten years. These aspects are the quickening pace of international exchange and its implications for the exporting of higher education models; the drive towards delegating responsibility away from central administration down to the regional level of government and, finally, the issue of the accompanying shift in political values and political theory which is involved in reassessing the role of the State in higher education
Keywords: educación superior; Europa; Revista Española de Pedagogía